Prone versus lateral position in acute hypoxemic respiratory failure patients with HFNO therapy: study protocol for a multicentre randomised controlled open-label trial - Xixin Zhou; Xiaoqing Luo; Qin Li; Guihua Chen; Jin Tong; Wang Deng (Trials, 2023)
Abstract Background High-flow nasal oxygen (HFNO) therapy is a leading treatment technique for acute hypoxemic respiratory failure (AHRF), but its treatment failure rate remains high. The awake prone position (APP) has been proven to increase oxygenation and reduce the endotracheal intubation rate in patients with COVID-19-induced AHRF. However, the APP is poorly tolerated in patients, and its performance in improving prognoses is controversial. The lateral position has a similar mechanism and effect to the prone position, but it is more tolerable than the prone position. Therefore, it is worth exploring whether the lateral position is better for awake patients with AHRF. Methods This is a protocol for a three-arm parallel-group multicentre randomised controlled open-label exploratory trial. A total of 583 patients from two hospitals in Chongqing, China, will be randomised to take the semi-recumbent position, lateral position, or prone position at a ratio of 1:1:1. Patients are all diagnosed with AHRF secondary to non-COVID-19 pneumonia or lung infection and receiving HFNO therapy. The primary outcome is ventilator-free days in 28 days. The secondary outcomes are the 28-day intubation rate, 28-day all-cause mortality, total position change time, the incidence of adverse events, number of hours using HFNO therapy, length of hospital and intensive care unit (ICU) stay, and others. We will conduct subgroup analyses on the arterial partial pressure of oxygen to the fraction of inspiration oxygen (PaO2/FiO2) ratio (> 200 mmHg or ≤ 200 mmHg), time from admission to intervention implementation (< 24 h or ≥ 24 h), position changing time, and different diagnoses. Discussion This trial will explore the prognostic effects of the APP with that of the lateral position in awake patients with non-COVID-19AHRF and compare the differences between them. To provide evidence for clinical decision-making and further research on position management. Trial registration This trial was registered in the Chinese Clinical Trial Registry. The registration number is ChiCTR2200055822 . Registered on January 20, 2022.